PERSPECTIVE TECHNOLOGIES FOR THE USE OF PRESERVATIVES IN THE PRODUCTION OF FOOD PRODUCTS - Shegelman I. R., Vasilyev A. S., Smirnova L. O. (A breakthrough in science: development strategies, 2018)
Russian scientists and inventors are actively researching the development of new methods. The developments patented for the use of preservatives in food production are given.
Keywords: патент; консерванты; patent; food production; производство пищевых продуктов; preservatives